An econometric market model of capital and investment inspired by Haavelmo - Erik Biørn (University of Oslo, Department of Economics, 2012)
In the paper steps are taken towards integration of two parts of Trygve Haavelmo's work: investment theory and econometrics of interrelated markets. Attempts are made to bring the duality in the representation of the capital service price and the capital quantity in relation to the investment price and quantity into the foreground, by confronting it with elements from simultaneous equation modeling of vector autoregressive systems with exogenous variables (VARX), using linear four-equation models. The role of the interest rate and the modeling of the expectation element in the capital service price and the capital's retirement pattern, and their joint effect on the model's investment quantity and price dynamics are discussed. Simulation experiments illustrate some of the theoretical points. An extension relaxing geometric decay is outlined.
Keywords: C32; C62; E22; E27; 330; Investment theory; Econometrics of investment; Stock-flow interaction; Dynamic stability; Capital retirement; Price expectation; Duality; Final form; ARMAX; Volkswirtschaftliche Investitionstheorie; Dynamisches Modell; Theorie